Re:Search - The Australian remote, regional and rural research database. - McManus, Alexandra; White, James (Curtin Health Research Innovation Institute (CHIRI) and Research Australia, 2010)
As a leader in health and nutrition research, CESSH is developing a suite of tools intended to make research findings easily accessable to both industry and the public, and to foster a spirit of collaboaration among like-minded researchers across the country.CESSH places high value on building relationships with research institutes throughout Western Australia and nationally. With this goal in mind, and in collaboration with Research Australia, CESSH is building a database of Australian institutes interested in any aspect of health research, including both specific topics (such as nutrition, chronic disease, or women's health) and broader health themes (such as health services, workforce, policies, and community development). Dubbed "Re:Search", this tool enables researchers to find others in their area, or nationally, with similar goals. The database carries a special emphasis on remote, rural and regional issues and, as such, will be of special benefit to those located away from major centres.